AN ENGLISH AND SIGN LANGUAGE HANDOUT FOR DEAF LEARNERS - Emi Fitri Audina; Iwan Supardi; Urai Salam (Universitas Tanjungpura, 2020)
AbstractThis research was conducted to design English and Sign Language handout for Deaf Learners. The purpose of this research was to find out whether English and Sign Language Handout was able to teach deaf learners vocabulary. The form of this research was developmental research. This developmental research was conducted to create a recent learning media for deaf learners. The method of this research consists of three phases namely analyzing, designing, and developing or called ADD. In designing the product the data were collected through observation sheet, video recorder, and camera. The designed product introduced English at the very first place through the sign language, material design, drill and practice. It consisted of five chapters; alphabet, numbers, greeting, introduction, and color. Keywords: Deaf Learners, Developmental Research, English and Sign Language Handout